Exploring the community structure of Afrotropical macroinvertebrate traits and ecological preferences along an agricultural pollution gradient in the Kat River, Eastern Cape, South Africa - Frank C. Akamagwuna; Oghenekaro N. Odume; Nicole B. Richoux (Ecological Indicators, 2022)
Agricultural activities impact riverine ecosystem structure, function, and processes. In the Afrotropical regions, research on agricultural effects on macroinvertebrate trait distribution is sparse. In this study, we investigated the spatial and temporal changes in the community structure of macroinvertebrate traits along an agricultural disturbance gradient in an Afrotropical River system. Physicochemical variables were sampled alongside macroinvertebrates at eight sites in the dry (winter and spring) and wet (summer and autumn) periods of 2018–2019. We grouped the sites into four categories using the percentage of agricultural land-use cover within each drainage area. Our results showed that agricultural pollution exhibited varying effects on traits and ecological preferences, with traits such as a predatory lifestyle, medium body-size (>10–20 mm), active swimming, possession of spiracles and haemoglobin, and adult aquatic life stage increasing with the pollution gradient. These traits were positively associated with nutrients (PO4+-P, NO2+-N, NH4+-N and NO3+-N), salinity, turbidity and temperature and were deemed tolerant of agricultural pollution. Shredding, crawling, and a preference for macrophytes as food showed strong positive associations with the least disturbed sites and were negatively associated with increasing nutrients, salinity, turbidity and water temperature. As such, these three traits were considered sensitive to agricultural pollution. The identified indicator traits can be used to predict the survival and distribution patterns of organisms under the impact of agriculture-induced stress.